Political Commitment in Managing Border Tourism - Elyta Elyta; Syarif Redha Fachmi Al Qadrie; Herlan Herlan; Syarifah Nurma Afhiani; Syarif Usmulyadi (Politicon : Jurnal Ilmu Politik, 2023)
This paper aims to analyze Political Commitment in managing border tourism in Kapuas Hulu District. The border is one of the potentials owned by Indonesia for the development of boundaries, such as tourism activities in Kapuas Hulu Regency, West Kalimantan. From this context, the explorative potential of the Regency is quite diverse, regarding nature, culture and adventure tourism. This is in line with the challenges encountered in the management of border tourism, such as the lack of supporting facilities, as well as the formation of cooperation and capital in managing exploration toward superiority. Furthermore, political commitment is needed in the management and development of border tourism, specifically through three aspects, namely verbal (expressed), institutional, and budgetary. By using a qualitative descriptive method, Political Commitment in the management of border tourism was analyzed. The data collection process also emphasized interviews with related parties, as secondary information sources included books, scientific journals, mass media, and documents from existing survey institutions.